-7x+11=60

Simple and best practice solution for -7x+11=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x+11=60 equation:


Simplifying
-7x + 11 = 60

Reorder the terms:
11 + -7x = 60

Solving
11 + -7x = 60

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + -7x = 60 + -11

Combine like terms: 11 + -11 = 0
0 + -7x = 60 + -11
-7x = 60 + -11

Combine like terms: 60 + -11 = 49
-7x = 49

Divide each side by '-7'.
x = -7

Simplifying
x = -7

See similar equations:

| -2x-4=-x+0 | | (t+3)(t+8)=t(t+5)+168 | | 18-2z=6-4 | | -6y=36x-72 | | 2x^3+4x^2+10x=0 | | 7x-2=34+x | | 4y+7y=66 | | 5n+10-8=2x | | 13a+50=360 | | 2(x-7)+3(x-1)=4+3 | | 4x+4y=-32 | | X+18=-4 | | 2y^2-7=25 | | x-4/8=15 | | -3(8x+2)+4(5x-1)= | | (3x^2y-xy)dx+(2x^3y^2+x^3y^4)dy=0 | | 3/5x-4=2 | | x-14=66 | | -5x-6=x-48 | | 4(-5x+8)-(x+5)=-15 | | 9xm+19=55 | | 4(-3x-6)= | | m(m-7)= | | 2*x-7=1 | | -2w-3(4z-5w)-32= | | 4c-3d=-20 | | 2x^2+4x-31=0 | | 3+ln(27x)=18-2ln(x) | | 2(y+3y)=84 | | 7(7x+6y-9)+4(8x-4)= | | -9x-10+3x-4= | | 3*x+4=1 |

Equations solver categories